HSBC : facilitating trade finance through blockchain - Sahay, Arvind; Tiwari, Tara (London : Indian Institute of Management, Ahmedabad, 2020)
In March 2020, Akash Munjal, Senior Vice President, Product Management-Global Trade and Receivable Finance, HSBC, was reviewing the transactions that his team had executed using the blockchain-based platform Contour. HSBC and ING had executed the first commercially viable trade transaction through blockchain for Cargill's shipment of soybeans from Malaysia to Argentina. The transaction had been completed via Corda, R3's blockchain platform.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Banks and banking, International -- Case studies; International business enterprises -- Finance -- Case studies; Blockchains (Databases) -- Case studies